Dirty pretty things [videorecording (DVD)] - Audsley, Mick; Buric, Zlatko, 1953-; Dicks-Mireaux, Odile; Ejiofor, Chiwetel; Frears, Stephen; Holmes, Rebecca; Knight, Steven, 1959-; Larson, Nathan, 1970-; Longhurst, Graham; López, Sergi, 1965-; Luczyc-Wyhowski, Hugo; Menges, Chris, 1940-; et al. (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2004)
Okwe is an illegal immigrant living in London. He was a doctor in his homeland and now works two jobs - during the day as a taxi driver, at night as a hotel desk clerk. When a prostitute tells him there's a mess in one of the hotel's bathrooms, Okwe finds a human heart in the toilet. Using his previous knowledge of medicine, he begins to solve the case of where the heart came from and soon delves into the world of body organ black-markets. He finds that his only friend, Senay, a Turkish illegal immigrant chambermaid, may be next to be used for organ parts.